Identification of QTL for resistance to root rot in sweetpotato (Ipomoea batatas (L.) Lam) with SSR linkage maps - Ma, Zhimin (BMC Genomics, 2020)
BACKGROUND: Sweetpotato root rot is a devastating disease caused by Fusarium solani that seriously endangers the yield of sweetpotato in China. Although there is currently no effective method to control the disease, breeding of resistant varieties is the most effective and economic option. Moreover, quantitative trait locus (QTL) associated with resistance to root rot have not yet been reported, and the biological mechanisms of resistance remain unclear in sweetpotato. Thus, increasing our knowledge about the mechanism of disease resistance and identifying resistance loci will assist in the development of disease resistance breeding. RESULTS: In this study, we constructed genetic linkage maps of sweetpotato using a mapping population consisting of 300 individuals derived from a cross between Jizishu 1 and Longshu 9 by simple sequence repeat (SSR) markers, and mapped seven QTLs for resistance to root rot. In total, 484 and 573 polymorphic SSR markers were grouped into 90 linkage groups for Jizishu 1 and Longshu 9, respectively. The total map distance for Jizishu 1 was 3974.24 cM, with an average marker distance of 8.23 cM. The total map distance for Longshu 9 was 5163.35 cM, with an average marker distance of 9.01 cM. Five QTLs (qRRM_1, qRRM_2, qRRM_3, qRRM_4, and qRRM_5) were located in five linkage groups of Jizishu 1 map explaining 52.6–57.0% of the variation. Two QTLs (qRRF_1 and qRRF_2) were mapped on two linkage groups of Longshu 9 explaining 57.6 and 53.6% of the variation, respectively. Furthermore, 71.4% of the QTLs positively affected the variation. Three of the seven QTLs, qRRM_3, qRRF_1, and qRRF_2, were colocalized with markers IES43-5mt, IES68-6 fs**, and IES108-1 fs, respectively. CONCLUSIONS: To our knowledge, this is the first report on the construction of a genetic linkage map for purple sweetpotato (Jizishu 1) and the identification of QTLs associated with resistance to root rot in sweetpotato using SSR markers. These QTLs will have practical significance for the fine mapping of root rot resistance genes and play an important role in sweetpotato marker-assisted breeding.